Penerapan desain interaksi pada perancangan e-commerce pabrik sepatu lokal LeePoure sebagai strategi untuk meningkatkan penjualan - Intan Marcelia Supono; Teguh Wahyono (AITI, 2026)
The rapid growth of the e-commerce industry in Indonesia is driven by several factors, including increased availability of internet access and changing consumer behavior. As a local shoe factory, LeePoure faces the challenge of developing and transforming its e-commerce platform to improve customer experience and increase online sales. Therefore, the purpose of this study is to analyze and design an effective interaction design for LeePoure's independent e-commerce platform with a User-Centered Design (UCD) approach. The research process involves user interviews to understand user needs and expectations, persona analysis to represent key user characteristics, prototyping, and usability testing to evaluate the effectiveness and usability of the proposed design. The results show that an interface design that emphasizes intuitive navigation, responsive display, and security of the transaction features can significantly enhance user convenience and satisfaction. These improvements are expected to support higher user engagement, increase online sales performance, and strengthen LeePoure’s competitiveness in the increasingly competitive e-commerce market.